2018
DOI: 10.1177/1524839918763585
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Posters Serve as a Low-Cost Option for Physical Activity Promotion of Hospital Nurses

Abstract: Hospital nurses play an important role in the nation's short- and long-term patient care. At the same time, nurses often experience high levels of occupational stress and participate in low levels of physical activity (PA). The purpose of this study was to examine the impact of self-monitoring and a poster campaign on the PA behaviors of hospital nurses. Motivational and instructional exercise posters were hung in break rooms of experimental units and replaced biweekly for 8 weeks. A total of 26 nurses (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Exercise programmes, tailored to meet personal interests, can be delivered by mobile phone, email or website. For example, a self-care poster campaign along with personalised physical activity feedback could be used to encourage nurses to interact with colleagues, set personal goals and self-monitor progress (Raney & Zanten, 2019). Additionally, several sessions of progressive muscle relaxation combined with music could be offered to ICU nurses to help reduce their stress and fatigue levels, thus improving resilience (Ozgundondu & Metin, 2019).…”
Section: Rele Vant To Clini C Al Pr Ac Ticementioning
confidence: 99%
“…Exercise programmes, tailored to meet personal interests, can be delivered by mobile phone, email or website. For example, a self-care poster campaign along with personalised physical activity feedback could be used to encourage nurses to interact with colleagues, set personal goals and self-monitor progress (Raney & Zanten, 2019). Additionally, several sessions of progressive muscle relaxation combined with music could be offered to ICU nurses to help reduce their stress and fatigue levels, thus improving resilience (Ozgundondu & Metin, 2019).…”
Section: Rele Vant To Clini C Al Pr Ac Ticementioning
confidence: 99%
“…Recent research has assessed challenges to effective health messaging in migrant populations [2022], and efficacy of visual health messaging to populations with low literacy [1, 23, 24], but most studies have been conducted in high-income countries. Posters as health promotion tools are appealing as they are a low-cost intervention that can potentially reach a wide audience [25], and are commonly used in health promotion programs in low-income countries. However, a 1989 study in India found that posters were often misinterpreted because of specific local understandings of the images, and piloting of posters in target communities was recommended [26].…”
Section: Introductionmentioning
confidence: 99%